ANALISA PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN YAMAHA MIO DI TELUKJAMBE KARAWANG BARAT - Ajat Sudrajat; Muhammad Fauzan Habibie; Rudy Ramadhan (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2020)
One's buying behavior towards a product purchases a lotfactor. Everyone has different desires and tastes.Product quality is a crucial factor in the decisionpurchase, besides that there are still many other factors that influence behaviorthe purchase.This research is to analyze the effect of product quality,promotion of purchasing decisions for Yamaha motorcycle productsAlso analyze the variables that have the most dominant influenceon the decision to purchase Yamaha Mio motorcycle products to the publicin the Teluk Jambe region.The population in this study is motorcycle consumersYamaha Mio in the Surakarta region. The sample used was 100respondents with the Accidental Quota Sampling technique. Data collection techniqueswith a questionnaire, while the data analysis technique uses regression analysismultiple linear, classic assumptions (normality test, multicollinearity test, testheteroscedasticity), statistical tests (t test, F test and coefficient of determination).From the results of the analysis of classical assumptions, normality test with kolmogorovsmirnovObtained significantly greater than 0.05, which means the data distributionnormal. Multicollinearity test obtained by the value of VIF and Tolerance obtainedone regression model can be canceledmulticollinearity, while the heteroscedasticity test using the Glejser methoddeclare no problem.Based on the results of multiple linear regression analysis of the t test obtainedProduct quality is significant todecision to purchase Yamaha Mio motorcycle products, while the promotion andsignificant significance at 5% tarap. From the test resultssimultaneous influence of product quality, promotiondecision to purchase a Yamaha Mio motorcycle product where the calculated F value> Ftable. The most dominant product qualitypurchase of Yamaha Mio motorcycle products. Obtained an R square value of0.255, which means that the dependent variable can be understood by the independent variableof 25.5% while the remaining 74.5% is approved by other variables